2021
DOI: 10.1159/000515088
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Higher Blood Pressure and Worse Renal Function in Salt-Sensitive Hypertension

Abstract: <b><i>Background:</i></b> The underlying pathogenesis of patients with salt-sensitive hypertension expressing higher blood pressure and severer renal damage remains uncertain. <b><i>Methods:</i></b> We recruited 329 subjects, 131 in salt-sensitive (SS) group, 148 in nonsalt-sensitive (NSS) group, and 50 healthy people in normal group and tested their renal function, 24-h ambulatory blood pressure, and growth factor series. <b><i>Results:</i><… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The main physiological function of the kidney is to regulate water, electrolytes, blood volume, and excrete metabolites in the body. Renal dysfunction can lead to water and sodium retention and increased blood volume, resulting in increased blood pressure ( 24 ). Fourth, the vascular mechanism (i.e., endothelial dysfunction and the nitric oxide pathway).…”
Section: Discussionmentioning
confidence: 99%
“…The main physiological function of the kidney is to regulate water, electrolytes, blood volume, and excrete metabolites in the body. Renal dysfunction can lead to water and sodium retention and increased blood volume, resulting in increased blood pressure ( 24 ). Fourth, the vascular mechanism (i.e., endothelial dysfunction and the nitric oxide pathway).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Chu et al, in 329 subjects looked at growth factors that are produced in relation to the activation of the phosphoinositide 3-kinase/ Ak strain transforming (PI3K-Akt) pathway, which is activated through serine and/or threonine phosphorylation of a range of downstream substrates ( 169 ). They found that individuals with SSBP had elevated levels of several growth factors compared to salt resistant group ( 169 ). The signal transduction PI3K-Akt Pathway regulates metabolism, proliferation, cell survival, growth and angiogenesis ( 170 ).…”
Section: Dietary Salt In Hypertensive Heart Disease and Its Complicat...mentioning
confidence: 99%
“…Functional impairment of the kidneys is also a frequent disorder in the presence of high blood pressure, also known as hypertension. It has been thought that renal damage linked to hypertension is caused by oxidative stress [ 146 , 147 , 148 ]. In this regard, ALA has also been tested for its antioxidant role in hypertension-induced kidney injury.…”
Section: Miscellaneousmentioning
confidence: 99%